Characterization of the Nutritional Composition of a Biotechnologically Produced Oyster Mushroom and its Physiological Effects in Obese Zucker Rats. Issue 22 (13th October 2020) - Maheshwari, Garima; Gessner, Denise K.; Meyer, Sandra; Ahlborn, Jenny; Wen, Gaiping; Ringseis, Robert; Zorn, Holger; Eder, Klaus
Abstract : Scope: Sustainable protein sources are needed to meet the increasing protein demands of a continuously growing world population. This study is focused on the biotechnological production of a protein rich oyster mushroom ( Pleurotus sajor‐caju ; PSC) by valorization of an agricultural side stream and the evaluation of the physiological effects of PSC in a rat model of metabolic syndrome. Methods and results: PSC is produced via submerged cultivation in a 150 L bioreactor that utilizes isomaltulose molasses as its sole carbon source, and is further analyzed for its nutritional composition. A feeding trial is performed using Zucker rats which are fed a 5% PSC supplemented diet, for 4 weeks. Biochemical analyses reveal a significant reduction of the liver lipid concentrations and liver inflammation in the PSC fed obese rats in comparison to the obese rats from the control group. Hepatic qPCR analyses, differential transcript profiling, and enzyme activity measurements reveal a number of altered pathways that may be responsible for these anti‐steatotic and anti‐inflammatory effects of the mushroom. Conclusion: Bioconversion of a low quality agricultural side stream to an improved protein source is performed by submerged cultured PSC, and the obtained mycelium shows strong anti‐steatotic and anti‐inflammatory effects. Abstract : Biotechnological upcycling of isomaltulose molasses by an oyster mushroom, Pleurotus sajor‐caju, results in the production of an alternative protein. The physiological effects of the biomass are evaluated in a feeding trial with Zucker rats. At the end of 4 weeks, addition of 5% Pleurotus sajor‐caju to the feed of obese Zucker rats results in decreased hepatic steatosis and inflammation.